A note on (gDF)-spaces - Renata R. del-Vecchio; Dinamérico P. Pombo; Cybele T. M. Vinagre (International Journal of Mathematics and Mathematical Sciences)
Certain locally convex spaces of scalar-valued mappings are shown to be finite-dimensional.